(untitled) (Observatorio Económico, 2013)
The year 2013 will begin with the same concern about stagnation in the developed economies: experts’ expectations point to growth of 1.6% for these economies, only a few tenths of a percentage point above the growth recorded in 2012 and well below growth prior to the 2008 crisis. Nevertheless, despite this negative external environment, the impact on the Chilean economy has turned out to be rather marginal, except for the fruit sector, where a slowdown has indeed been observed in recent months. Continue reading...